Steel slag-mineral slag efficient grinding preparation process
By mixing steel slag with slag in a specific proportion, and using vertical milling and ball milling equipment combined with grinding aids, the problems of poor abrasionability of steel slag and volume expansion of hydration reactions are solved, efficient grinding of composite gelling materials and optimized gelling performance are achieved, and the mechanical properties and long-term stability of the material are improved.
Patent Information
- Application Number
- CN202510003580.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-18
AI Technical Summary
Steel slag is poorly easily wearable during gelation and utilization, resulting in low grinding efficiency. The volume expansion phenomenon in the hydration reaction may lead to poor phenomena such as cracks and deformation of the material structure, affecting long-term performance and stability.
A specific proportion of steel slag is used to mix with the slag, and used in combination with the vertical milling and ball milling equipment, combined with the addition of abrasive agent, the particle size of the mixture is gradually refined to 10-50 μm to form a composite gelling material. At the same time, retarder is added to regulate the hydration reaction process and reduce volume expansion and internal stress.
The grinding efficiency of steel slag-slag is significantly improved, the particle size distribution and gelling performance of composite gelling materials are optimized, the compressive strength and durability of the material are enhanced, and structural defects caused by excessive hydration reaction are avoided.
Smart Images

Figure BDA0005226195910000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of environmentally friendly cementitious materials, and more specifically, to a high-efficiency grinding and preparation process for steel slag-mineral slag. Background Art
[0002] With the rapid development of modern industry, a large amount of solid waste has been generated in industries such as steel and nonferrous metal smelting, among which steel slag and slag are the two most common and large types of industrial waste. The accumulation of these steel slag and slag not only occupies a large amount of land resources, but also poses a potential threat to the surrounding soil, water and air environment, causing a series of environmental problems, such as land pollution, groundwater pollution and dust pollution.
[0003] Traditionally, the treatment of steel slag and slag is relatively extensive, mainly landfill or stacking, and only a small amount is used for low added value, and the resource utilization rate is extremely low. However, in recent years, with the continuous improvement of people's environmental awareness and the popularization of the concept of sustainable development, the resource utilization of industrial solid waste has become a research hotspot. Steel slag and slag contain rich elements such as silicon, calcium, and aluminum, and have potential gelling activity. If they can be effectively converted into gelling materials, it can not only solve environmental problems, but also create considerable economic benefits and realize the recycling of resources.
[0004] However, there are many technical problems in the gelation and utilization of steel slag. First, steel slag has poor grindability. It is rich in iron oxide compounds, which significantly increase the hardness of steel slag. Compared with other conventional materials, it is difficult to effectively crush and refine steel slag particles when using traditional ball mills for grinding. Secondly, when the ground steel slag is used in the subsequent process, the calcium, magnesium and other elements in it will form hydration products such as Ca 2 + Mg 2+ Related compounds, these hydration products will expand in volume during the reaction process. This volume expansion will generate internal stress in concrete or other building materials made of steel slag, which may cause cracks, deformation and other undesirable phenomena in the material structure over time, seriously affecting the long-term performance and stability of the building materials. Summary of the invention
[0005] In order to solve the above problems, the present application provides a steel slag-slag efficient grinding preparation process.
[0006] The present application provides a steel slag-slag high-efficiency grinding preparation process using the following technical solutions: A high-efficiency grinding process for preparing steel slag-ore slag comprises the following steps: Mixing steel slag and ore slag in a mass ratio of 4:(6-7) to obtain a steel slag-ore slag mixture; The slag-slag mixture is ground with a vertical mill, the speed is set at 20-30 rpm, the pressure is 8-12 MPa, the ventilation volume is 3000-5000 m3 / h, the slag-slag mixture is ground to a particle size of 0.5-1 mm, and rough grinding is completed; The steel slag-slag mixture after coarse grinding is ground by a ball mill, the ball-to-material ratio in the ball mill is controlled at (4-6):1, the rotation speed is set at 15-25 rpm, a grinding aid is added to the ball mill, the amount of the grinding aid added is 1-5% of the total mass of the steel slag and the slag, the steel slag-slag mixture is ground to a particle size of 10-50 μm, and fine grinding is completed to obtain a steel slag-slag composite cementitious material.
[0007] By adopting the above technical scheme, by mixing steel slag and slag in a specific proportion, the relatively good grindability of slag and its complementarity with steel slag in cementitious properties are utilized to improve the grindability of the overall material and optimize the performance of the composite cementitious material. The vertical mill can effectively reduce the particle size of the mixture to 0.5-1mm for coarse grinding. Its reasonable speed, pressure and ventilation volume settings can reduce energy consumption while ensuring the grinding effect. The ball mill can further refine the particle size to 10-50μm for fine grinding, so that it can play a better role in the application of building materials, such as improving the strength and durability of concrete.
[0008] Optionally, the grinding aid includes one or more of polyethylene glycol, triethanolamine, glycerol, and neopentyl glycol.
[0009] By adopting the above technical solution, these organic amines and alcohols have good surface activity. They can be adsorbed on the surface of steel slag-slag particles, reduce the surface energy of the particles, reduce the agglomeration phenomenon between particles, and make the particles easier to be broken and refined by the grinding medium during the grinding process. At the same time, the adsorption layer formed by the grinding aid on the particle surface can play a certain lubricating role, reduce the friction during the grinding process, improve the grinding efficiency, help solve the problem of poor grindability of steel slag, reduce grinding time and energy consumption, and make the particle size distribution of the final composite cementitious material more uniform, thereby improving the stability of its gelling properties.
[0010] Optionally, the grinding aid includes 20-30% triethanolamine phosphate, 15-25% polyethylene glycol, 10-15% sodium lignin sulfonate, 5-10% sodium stearate, 3-8% sodium silicate, 2-5% tetrabutyl titanate, 10-15% sodium polyacrylate, and the rest is water.
[0011] By adopting the above technical scheme, triethanolamine phosphate has good surface activity and metal ion complexing ability, can complex with metal ions such as iron oxide compounds in steel slag, reduce the internal chemical bond force of particles, and adsorb on the surface of particles to reduce surface energy, promote particle crushing and refinement. Polyethylene glycol forms a lubricating film to reduce friction, reduce energy loss and prevent particle agglomeration. Sodium lignin sulfonate enhances the dispersibility of the grinding aid system in water, gives particles a negative charge to generate electrostatic repulsion to prevent agglomeration. Sodium stearate acts as a lubricant to further reduce the friction coefficient and form a colloid to wrap the particles to play an isolating and dispersing role. Sodium silicate reacts with the active ingredients of steel slag to generate low-melting-point and high-fluidity silicate substances, which drive the internal particle crushing and refinement and improve the surface properties. Tetrabutyl titanate is hydrolyzed to form a nano titanium dioxide film to enhance the hardness and wear resistance of the particles and may affect the crystal morphology and growth process of the hydration product. Sodium polyacrylate maintains the stability and dispersibility of the grinding aid system. In summary, the grinding aid formula can significantly improve the grinding efficiency of steel slag-mineral slag, improve particle characteristics, and is beneficial to the improvement of the cementitious properties and long-term stability of composite cementitious materials.
[0012] Optionally, the diameters of the grinding balls used in the ball milling process are 60 mm, 40 mm, and 20 mm, respectively, and the number ratio of the grinding balls with diameters of 60 mm, 40 mm, and 20 mm is 1:2:3.
[0013] By adopting the above technical solution, the large diameter (60mm) grinding balls are mainly responsible for the strong impact on the coarse particles during the ball milling process, and use their large mass and kinetic energy to break the larger steel slag-slag agglomerates or coarse particles into smaller particles. The medium diameter (40mm) grinding balls further grind and refine the particles on the basis of the initial crushing of the large balls, and improve the shape and surface properties of the particles through collision with the particles and rolling and friction between the balls and the cylinder lining. The small diameter (20mm) grinding balls can fill the gaps between the large and medium balls to finely grind the already relatively small particles. The high frequency of collision and friction enables the particle size to reach the target range of 10-50μm, and makes the particle size distribution more uniform, which improves the efficiency and effect of ball milling and is conducive to the subsequent gelling properties of the composite cementitious material.
[0014] Optionally, a retarder is further added to the steel slag-slag composite cementitious material, and the amount of the retarder added is 0.5-2% of the mass of the steel slag-slag composite cementitious material.
[0015] By adopting the above technical solution, the addition of retarder can adjust the hydration reaction process of steel slag-slag composite cementitious material. Retarder can make the hydration heat release more uniform and reduce the risk of temperature stress cracks caused by concentrated hydration heat. In the utilization of steel slag gelation, by controlling the hydration reaction rate, more favorable conditions are provided for the formation of the internal structure of the material, thereby improving the long-term performance and stability of the material and avoiding structural defects caused by too fast hydration reaction.
[0016] Optionally, the retarder includes 30-40% sodium gluconate, 20-30% trisodium citrate, 15-25% metakaolin, 10-20% silica fume, and 5-10% aminotrimethylenephosphonic acid.
[0017] By adopting the above technical scheme, sodium gluconate and trisodium citrate can form stable complexes with metal ions such as calcium ions in steel slag, delay the hydration process of cement-based materials, reduce the concentration of free calcium ions in the solution, slow down the hydration reaction rate, and reduce the concentrated release of hydration heat. Metakaolin and silica fume have high volcanic ash activity and can react with steel slag hydration products, consume calcium hydroxide, etc., reduce the volume expansion caused by the crystal growth of calcium hydroxide, and at the same time fill the pore structure to improve the density of the material and improve the microstructure. Aminotrimethylenephosphonic acid forms chelates with metal ions to synergistically enhance the retarding effect, and affect the crystal morphology and growth process of the hydration product, reducing uneven volume changes and internal stress generation. This retarder formula effectively solves the problems of cracks and deformation in the material structure caused by the volume expansion of steel slag hydration products, and improves the long-term performance and stability of building materials based on steel slag-slag composite cementitious materials.
[0018] Optionally, the steel slag needs to be pretreated before mixing with the slag, and the pretreatment steps are: The steel slag is placed in a sealed heat-insulating container and heated to 350-450°C. Water is sprayed into the container to contact the steel slag to generate water vapor. The steam pressure in the container is maintained at 0.4-0.5MPa. The container is kept warm for 18-24 hours. After the insulation is completed, the steel slag is cooled, taken out and dried.
[0019] By adopting the above technical solution, the steel slag is heated to a certain temperature, water is sprayed to generate steam and the temperature is kept, so that the free calcium oxide and other components in the steel slag react with the water vapor, and the free calcium oxide is digested to generate calcium hydroxide. This process will expand the volume of the steel slag and make the internal structure loose, thereby reducing the hardness of the steel slag, improving its grindability, and reducing energy consumption and equipment wear in the subsequent vertical mill and ball mill process. At the same time, this pretreatment process can also transform some unstable mineral phases in the steel slag, reduce the volume expansion of the steel slag in the subsequent use process and other undesirable phenomena, which is conducive to improving the stability and quality of the steel slag-slag composite cementitious material, so that it can better play a gelling role in the application of building materials and maintain long-term performance.
[0020] Optionally, the specific method of spraying water is: take 3-6% of the total mass of the steel slag water, spray it on the surface of the steel slag at a uniform speed within 20-30 minutes, and wait for 10-15 minutes after each water spraying.
[0021] By adopting the above technical solution, water can be sprayed in a specific mass ratio and time interval to ensure that water and slag are in uniform and sufficient contact to generate steam. The uniform spraying makes the steam generation process relatively stable, avoiding excessive fluctuations in steam pressure or uneven reactions caused by spraying water too fast or too slow. The interval time allows the steam to have enough time to diffuse and react inside the slag, so that the internal structure of the slag is more evenly destroyed and improved, further improving the effect of slag pretreatment, better reducing the hardness of the slag and optimizing its performance, and laying a good foundation for the subsequent mixing, grinding, and preparation and application of cementitious materials.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application mixes steel slag and blast furnace slag in a mass ratio of 4:(6-7), the grindability of the blast furnace slag is significantly improved and the performance of the composite cementitious material is optimized by virtue of its good grindability and complementary cementitious properties with the steel slag. The composite cementitious material prepared by the vertical mill, ball mill and grinding aid can effectively improve key performance indicators such as concrete strength and durability when applied in the construction field, providing strong support for the quality improvement of construction materials and the comprehensive utilization of resources.
[0023] 2. In the preferred grinding aid formula of the present application, triethanolamine phosphate is used with the help of surface activity and metal ion complexing ability, polyethylene glycol relies on lubricating film, sodium lignin sulfonate relies on enhancing dispersibility, sodium stearate reduces the friction coefficient and forms a colloid, sodium silicate reacts with the active components of steel slag, tetrabutyl titanate is hydrolyzed to form a nanofilm, and sodium polyacrylate maintains the stability of the system. The synergistic effect of each component significantly improves the grinding efficiency of steel slag-slag, optimizes the particle characteristics, and effectively guarantees its long-term stability while enhancing the gelling properties of the composite cementitious material, laying a solid foundation for the efficient utilization of steel slag-slag and the improvement of the quality of related building materials.
[0024] 3. The method of the present application, by adding a retarder accounting for 0.5-2% of the mass of the steel slag-slag composite cementitious material, can effectively regulate the hydration reaction process of the composite cementitious material, promote the uniform release of hydration heat, and significantly reduce the risk of temperature stress cracks caused by concentrated hydration heat. When the steel slag is gelled, the hydration reaction rate is accurately controlled to create better conditions for the construction of the internal structure of the material, effectively improve the long-term performance and stability of the material, effectively avoid structural defects caused by too fast hydration reaction, and ensure the reliability and durability of the building material during use. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0026] Preparation example of grinding aid Preparation Example 1 A preparation example of a grinding aid: Add 150 g of water, 250 g of triethanolamine phosphate and 200 g of polyethylene glycol into a reaction kettle with a stirring device, heat it to 50° C., turn on the stirrer, set the stirring speed to 300 rpm, and mix the two thoroughly.
[0027] Add 120 g of sodium lignin sulfonate and 80 g of sodium stearate into the reactor, raise the temperature in the reactor to 65°C, and keep stirring for 20 minutes; 50 g of sodium silicate and 30 g of tetrabutyl titanate were added to the reaction kettle and stirred continuously for 30 minutes. Finally, 120 g of sodium polyacrylate was added to the reaction kettle, stirred for 10 minutes, and cooled to room temperature to obtain a grinding aid.
[0028] Preparation Example 2 A preparation example of a grinding aid: The difference from Preparation Example 1 is that the grinding aid contains 200g of triethanolamine phosphate, 150g of polyethylene glycol, 100g of sodium lignin sulfonate, 50g of sodium stearate, 30g of sodium silicate, 20g of tetrabutyl titanate, 100g of sodium polyacrylate, and 350g of water.
[0029] Preparation Example 3 A preparation example of a grinding aid: The difference from Preparation Example 1 is that the grinding aid contains 300 g of triethanolamine phosphate, 200 g of polyethylene glycol, 150 g of sodium lignin sulfonate, 100 g of sodium stearate, 80 g of sodium silicate, 50 g of tetrabutyl titanate, 100 g of sodium polyacrylate, and 20 g of water.
[0030] Preparation example of retarder Preparation Example 4 Preparation example of a retarder: 250 g of metakaolin and 200 g of silica fume were placed in an oven and dried at 120° C. for 3 hours. After drying, the metakaolin and silica fume were ground and passed through a 300-mesh sieve respectively.
[0031] Put 300g of sodium gluconate and 200g of trisodium citrate into a high-speed blender, set the stirring speed to 600 rpm, and stir for 10 minutes to fully mix the two.
[0032] Slowly add the ground and sieved metakaolin and silica fume into the mixer while stirring. Adjust the stirring speed to 200 rpm and the stirring time to 20 minutes.
[0033] 50 g of aminotrimethylenephosphonic acid was added dropwise into the mixer. The stirring speed was kept constant during the addition. After the addition was completed, the mixture was stirred for another 30 minutes to make the aminotrimethylenephosphonic acid evenly distributed in the entire mixture to obtain a uniform retarder mixture.
[0034] Preparation Example 5 A preparation example of a retarder: The difference from Preparation Example 4 is that the retarder includes 400 g of sodium gluconate, 300 g of trisodium citrate, 150 g of metakaolin, 100 g of silica fume, and 50 g of aminotrimethylenephosphonic acid.
[0035] Preparation Example 6 A preparation example of a retarder: The difference from Preparation Example 4 is that the retarder includes 350 g of sodium gluconate, 250 g of trisodium citrate, 200 g of metakaolin, 150 g of silica fume, and 50 g of aminotrimethylenephosphonic acid. Example
[0036] Example 1 A high-efficiency grinding process for steel slag-ore slag: The steel slag shall be electric furnace slag, and the slag shall be granulated blast furnace slag; 40 kg of steel slag and 65 kg of slag were poured into a forced mixer for thorough mixing. The stirring speed of the mixer was set to 50 rpm and the stirring time was 10 minutes to ensure that the steel slag and slag were evenly mixed to obtain a steel slag-slag mixture.
[0037] Adjust the speed of the vertical mill to 25 rpm, the pressure to 10 MPa, and the ventilation volume to 4000 m 3 / h, the mixed steel slag-slag mixture is sent to the feed port of the vertical mill through the conveying equipment, and ground until it reaches 0.5-1mm to complete the coarse grinding. The coarsely ground materials that meet the particle size requirements are separated and conveyed to the next ball milling process, while the coarse particles that do not meet the particle size requirements are returned to the vertical mill for further grinding.
[0038] According to the requirement of ball-to-material ratio of 5:1, grinding balls with diameters of 60mm, 40mm, and 20mm are selected, and the number ratio is 1:2:3. The grinding balls are loaded into the cylinder of the ball mill, and the grinding aid is accurately weighed according to 3% of the total mass of the slag-slag mixture. The grinding aid can be selected from one or two or three of polyethylene glycol, triethanolamine, propylene glycol, and neopentyl glycol. In this embodiment, triethanolamine is selected, and the grinding aid is added to the slag-slag mixture inside the cylinder. Start the ball mill and set the speed at 20 rpm. Sample once every 30 minutes, use a laser particle size analyzer to detect the particle size of the material, and stop ball milling when the particle size reaches 10-50μm to obtain a slag-slag composite cementitious material.
[0039] Example 2 A steel slag-ore slag efficient grinding preparation process: The difference from Example 1 is that 40 kg of steel slag and 60 kg of ore slag are mixed.
[0040] Example 3 A steel slag-ore slag efficient grinding preparation process: The difference from Example 1 is that 40 kg of steel slag and 70 kg of ore slag are mixed.
[0041] Example 4 A steel slag-slag efficient grinding preparation process: The difference from Example 1 is that the grinding aid is prepared by Preparation Example 1.
[0042] Example 5 A steel slag-slag efficient grinding preparation process: The difference from Example 4 is that the grinding aid is prepared by Preparation Example 2.
[0043] Example 6 A steel slag-slag efficient grinding preparation process: The difference from Example 4 is that the grinding aid is prepared by Preparation Example 3.
[0044] Example 7 A high-efficiency grinding preparation process for steel slag-ore slag: The difference from Example 1 is that the diameter of the grinding balls used in the ball milling process is 40 mm.
[0045] Example 8 A steel slag-slag efficient grinding preparation process: The difference from Example 1 is that a retarder is also added to the steel slag-slag composite cementitious material, and the amount of the retarder added is 1% of the mass of the steel slag-slag composite cementitious material. The retarder is prepared by Preparation Example 4.
[0046] Example 9 A high-efficiency grinding preparation process for steel slag-ore slag: The difference from Example 8 is that the retarder is prepared by Preparation Example 5.
[0047] Example 10 A high-efficiency grinding preparation process for steel slag-ore slag: The difference from Example 8 is that the retarder is prepared by Preparation Example 6.
[0048] Embodiment 11 A steel slag-slag high-efficiency grinding preparation process: The difference from Example 1 is that the steel slag and the slag need to be pretreated before mixing, and the pretreatment steps are: The steel slag is put into a sealed insulation tank and heated to 400℃. 5% of the total mass of the steel slag is taken and sprayed on the surface of the steel slag at a uniform speed within 25 minutes. There is a 12-minute interval between each water spraying. The water contacts the steel slag to generate water vapor. The steam pressure in the container is maintained at 0.4-0.5MPa. The tank is kept warm for 22 hours. After the insulation is completed, it is cooled, the steel slag is taken out and dried to a moisture content of less than 1%.
[0049] Example 12 A high-efficiency grinding preparation process for steel slag-ore slag: The difference from Example 11 is that the steel slag is loaded into a sealed insulation tank, and the steel slag is heated to 400°C, and water is sprayed on the steel slag. The water contacts the steel slag to generate water vapor. The water spraying is stopped when the steam pressure in the container reaches 0.4-0.5MPa. The heat is kept for 22 hours. After the heat is completed, the steel slag is cooled, taken out and dried to a moisture content of less than 1%.
[0050] Comparative Example Comparative Example 1 A steel slag-slag efficient grinding preparation process: The difference from Example 1 is that 40 kg of steel slag is mixed with 40 kg of slag.
[0051] Comparative Example 2 A high-efficiency grinding preparation process for steel slag-ore slag: The difference from Example 1 is that the coarse grinding is not performed by a vertical mill.
[0052] Comparative Example 3 A steel slag-ore slag high-efficiency grinding preparation process: The difference from Example 1 is that no grinding aid is added.
[0053] Performance testing Detection Methods 10 kg of the composite cementitious materials prepared in the embodiment and the comparative example were taken respectively, and cubic specimens of 150 mm * 150 mm * 150 mm were made according to the standard of water-cement ratio = 0.6, and cured for 7 days and 28 days under standard curing conditions (temperature 20 ± 2 ° C, relative humidity above 95%). The mechanical properties were measured according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the specimens were observed during the hydration process for cracking, deformation and other problems.
[0054] Table 1 Experimental data It can be seen from Example 1 and Comparative Example 1 and Table 1 that in the steel slag-slag high-efficiency grinding preparation process, the amount of slag has a significant effect on the mechanical properties and appearance stability of the composite cementitious material. A suitable steel slag to slag mass ratio helps to improve the mechanical properties of the composite cementitious material and ensure its structural stability during the hydration process. When the amount of slag deviates from a reasonable range, the strength of the material will decrease, and it will be more prone to appearance defects caused by factors such as internal stress.
[0055] Combining Example 1 and Comparative Example 2 and Table 1, it can be seen that in Example 1, the steel slag-slag mixture is first coarsely ground to 0.5-1mm by a vertical mill and then subjected to subsequent ball milling and other processes. The composite cementitious material finally obtained exhibits good mechanical properties, with a 7-day compressive strength of 19.3Mpa and a 28-day compressive strength of 28.5Mpa, and no cracking or deformation in appearance; Comparative Example 2 omits the vertical mill coarse grinding step, and the corresponding composite cementitious material has a 7-day compressive strength of 18.3Mpa and a 28-day compressive strength of 25.4Mpa, and a small amount of cracks appear. This shows that vertical mill coarse grinding helps to improve the particle size and other states of the material, laying the foundation for subsequent ball milling and the improvement of the performance of the final composite cementitious material. The lack of this process will reduce the compressive strength of the material and affect the structural stability to a certain extent.
[0056] Combining Example 1 and Comparative Example 3 and Table 1, it can be seen that in Example 1, a grinding aid (triethanolamine is selected in the example) is added during the ball milling process, and the obtained composite gelling material has a 7-day compressive strength of 19.3Mpa, a 28-day compressive strength of 28.5Mpa, and a good appearance; Comparative Example 3 does not add a grinding aid, and its 7-day compressive strength of the composite gelling material is only 15.7Mpa, and the 28-day compressive strength is 23.8Mpa, and a small amount of cracks appear. It can be seen that the grinding aid can effectively improve the grinding efficiency of the material, make the particles more fully refined, and then improve the compressive strength of the composite gelling material, and help reduce the internal stress problems caused by factors such as particle state during the hydration process, and ensure the stability of the material appearance.
[0057] It can be seen from Examples 1-3 and Table 1 that when the mixing ratio of steel slag to slag changes within a certain range, it has an impact on the performance of the composite cementitious material. The mass ratio of steel slag to slag needs to be controlled within the range of this application to ensure that the composite cementitious material obtains relatively better mechanical properties and better structural stability. The ratio of Example 1 is the best in this application.
[0058] Combining Example 1 and Examples 4-6 with Table 1, it can be seen that Example 1 uses triethanolamine as a grinding aid, while Examples 4-6 respectively use the grinding aids prepared by Preparation Examples 1-3. From the compressive strength data, Example 4, Example 5, and Example 6 all improve the compressive strength of the composite cementitious material to a certain extent compared with Example 1, and there is no cracking or deformation in the appearance. This shows that the grinding aid formula of the preparation example of this application helps to further optimize the mechanical properties and stability of the material.
[0059] Combining Examples 1 and 7 with Table 1, it can be seen that Example 1 uses a combination of grinding balls with diameters of 60 mm, 40 mm, and 20 mm and a quantity ratio of 1:2:3, and the obtained composite cementitious material has a 7-day compressive strength of 19.3 MPa and a 28-day compressive strength of 28.5 MPa, and no cracking or deformation in appearance; Example 7 uses grinding balls with a diameter of 40 mm, and its 7-day compressive strength is reduced to 18.6 MPa, and its 28-day compressive strength is 28.1 MPa, and a small amount of cracks appear. This shows that the grinding ball diameter combination of the present application can more effectively crush and refine the material, so that the particles reach an ideal particle size distribution, thereby ensuring that the composite cementitious material has good mechanical properties and appearance stability. A single grinding ball diameter cannot fully exert the ball milling effect, resulting in a decrease in material performance.
[0060] Combining Example 1 and Examples 8-10 and Table 1, it can be seen that the addition of retarders and retarders of different formulations have a positive effect on the performance of steel slag-slag composite cementitious materials. No retarder was added in Example 1, and Examples 8-10 respectively used retarders prepared by Preparation Examples 4-6. From the compressive strength data, compared with Example 1, Examples 8, 9, and 10 have improved compressive strength, and there is no cracking or deformation in appearance. Retarder can regulate the hydration reaction process of composite cementitious materials and optimize the formation of the internal structure of the material. Different formulations of retarders will produce different degrees of performance improvement effects due to differences in composition and proportion. Reasonable selection of retarders helps to further improve the mechanical properties and long-term stability of the material. The ratio of Preparation Example 6 in this application is the best in this application.
[0061] Combining Example 1 and Examples 11-12 and Table 1, it can be seen that the pretreatment method of steel slag has an impact on the performance of steel slag-slag composite cementitious materials. Example 1 did not perform specific pretreatment on the steel slag. Example 11 adopted the pretreatment steps of placing the steel slag in a sealed insulation tank, heating it to 400°C, spraying water at intervals, controlling steam pressure, insulation, and drying. Example 12 did not adopt the method of spraying water at intervals. The test data showed that the steel slag pretreatment process can improve the performance of the steel slag itself, and then help to improve the mechanical properties and structural stability of the composite cementitious materials. Different differences in water spraying treatments will cause certain fluctuations in the final material performance. The pretreatment method in Example 11 of the present application is the best.
[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-efficiency grinding process for steel slag-ore slag, characterized in that: The following steps are involved: Mixing steel slag and ore slag in a mass ratio of 4:(6-7) to obtain a steel slag-ore slag mixture; The steel slag-slag mixture is ground with a vertical mill, with the speed set at 20-30 rpm, the pressure at 8-12 MPa, and the ventilation volume at 3000-5000m 3 / h, grinding the steel slag-slag mixture to a particle size of 0.5-1 mm to complete coarse grinding; The steel slag-slag mixture after coarse grinding is ground with a ball mill, the ball-to-material ratio in the ball mill is controlled at (4-6):1, the rotation speed is set at 15-25 rpm, and a grinding aid is added to the ball mill, the amount of the grinding aid added is 1-5% of the total mass of the steel slag and the slag, the steel slag-slag mixture is ground to a particle size of 10-50 μm, and fine grinding is completed to obtain a steel slag-slag composite cementitious material.
2. The steel slag-slag high-efficiency grinding preparation process according to claim 1 is characterized in that: The grinding aid includes one or more of polyethylene glycol, triethanolamine, glycerol and neopentyl glycol.
3. The steel slag-slag high-efficiency grinding preparation process according to claim 1 is characterized in that: The grinding aid comprises 20-30% of triethanolamine phosphate, 15-25% of polyethylene glycol, 10-15% of sodium lignin sulfonate, 5-10% of sodium stearate, 3-8% of sodium silicate, 2-5% of tetrabutyl titanate, 10-15% of sodium polyacrylate, and the rest is water.
4. The steel slag-slag high-efficiency grinding preparation process according to claim 1 is characterized in that: The diameters of the grinding balls used in the ball milling process are 60 mm, 40 mm, and 20 mm, respectively, and the number ratio of the grinding balls with diameters of 60 mm, 40 mm, and 20 mm is 1:2:
3.
5. The steel slag-slag high-efficiency grinding preparation process according to claim 1 is characterized in that: A retarder is also added to the steel slag-slag composite gelling material, and the amount of the retarder added is 0.5-2% of the mass of the steel slag-slag composite gelling material.
6. The steel slag-slag high-efficiency grinding preparation process according to claim 5 is characterized in that: The retarder comprises 30-40% sodium gluconate, 20-30% trisodium citrate, 15-25% metakaolin, 10-20% silica fume and 5-10% aminotrimethylenephosphonic acid.
7. The steel slag-slag high-efficiency grinding preparation process according to claim 1 is characterized in that: The steel slag needs to be pre-treated before mixing with the slag, and the pre-treatment steps are: The steel slag is placed in a sealed heat-insulating container and heated to 350-450°C. Water is sprayed into the container to contact the steel slag to generate water vapor. The steam pressure in the container is maintained at 0.4-0.5MPa. The container is kept warm for 18-24 hours. After the insulation is completed, the steel slag is cooled, taken out and dried.
8. The steel slag-slag high-efficiency grinding preparation process according to claim 7 is characterized in that: The specific method of water spraying is: take 3-6% of the total mass of the steel slag water, spray it on the surface of the steel slag at a uniform speed within 20-30 minutes, and wait for 10-15 minutes after each water spraying.
Citation Information
Cited By
Steel slag grading and recycling method based on shallow grinding technology of ball mill
CN120532594A